Particle control via cryopumping and its impact on the edge plasma profiles of Alcator C-Mod - M.A. Miller; J.W. Hughes; S. Mordijck; M. Wigram; J. Dunsmore; R. Reksoatmodjo; R.S. Wilcox (Nuclear Materials and Energy)
At the high ne proposed for high-field fusion reactors, it is uncertain whether ionization, as opposed to plasma transport, will be most influential in determining ne at the pedestal and separatrix. A database of Alcator C-Mod discharges is analyzed to evaluate the impact of source modification via cryopumping. The database contains similarly-shaped H-modes at fixed IP=0.8 MA and Bt=5.4 T, spanning a large range in Pnet and ionization. Measurements from an edge Thomson scattering system are combined with those from a midplane-viewing Lyα camera to evaluate changes to ne and Te in response to changes to ionization rates, Sion. nesep and Teped are found to be most sensitive to changes to Sionsep, as opposed to neped and Tesep. Dimensionless quantities, namely αMHD and ν∗, are found to regulate attainable pedestal values. Select discharges at different values of Pnet and in different pumping configurations are analyzed further using SOLPS-ITER. It is determined that changes to plasma transport coefficients are required to self-consistently model both plasma and neutral edge dynamics. Pumping is found to modify the poloidal distribution of atomic neutral density, n0, along the separatrix, increasing n0 at the active X-point. Opaqueness to neutrals from high ne in the divertor is found to play a role in mediating neutral penetration lengths and hence, the poloidal distribution of neutrals along the separatrix. Pumped discharges thus require a larger particle diffusion coefficient than that inferred purely from 1D experimental profiles at the outer midplane.